Grazing Lands in Himachal Pradesh - Raina, V. (Indian Forester, 1960)
The word "Charand" as is used and known in Himachal Pradesh is applied to grazing lands owned by the Government and declared as protected forests wide Himachal Pradesh Government Notification No. Ft. 29-241-B/B/49 dated the 25th February, 1952, after declaring the provisions of Chapter IV of the Indian Forest Act (XVI of 1927) applicable to such lands. In this article is briefly discussed the present deplorable condition, their classification into three different altitudinal types, potential utility and social economic aspect of the graziers whose economy is intimately integrated with rearing of cattle, sheep, goats and other live stock.